Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0073162
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Methyl-Donor Supplementation Augments Colitis in Young Adult Mice

Abstract: Inflammatory bowel diseases (IBD) have become highly prevalent in developed countries. Environmentally triggered exaggerated immune responses against the intestinal microbiome are thought to mediate the disorders. The potential dietary origins of the disease group have been implicated. However, the effects of environmental influences on prenatal developmental programming in respect to orchestrating postnatal microbiome composition and predilection towards mammalian colitis have not been examined. We tested how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Epigenetic maturation relevant for intestinal immune regulation continues beyond infancy in mammals, indicating that even postnatally occurring DNA methylation changes may be important in IBD pathogenesis 14 . Furthermore, maternal micronutrient supplementation can induce colonic mucosal DNA methylation modification relevant for murine colitis susceptibility, implicating this epigenetic process in the developmental origins of IBD 13 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic maturation relevant for intestinal immune regulation continues beyond infancy in mammals, indicating that even postnatally occurring DNA methylation changes may be important in IBD pathogenesis 14 . Furthermore, maternal micronutrient supplementation can induce colonic mucosal DNA methylation modification relevant for murine colitis susceptibility, implicating this epigenetic process in the developmental origins of IBD 13 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Extension of these studies revealed that methyl donor supplementation during the prenatal period alone was sufficient to augment IBD risk, highlighting gestation as the critical developmental period for epigenetic changes that imprint sensitivity to mucosal injury, at least in this DSS model. 57 Interestingly, prenatal methyl donor exposure was also shown to induce changes in gut microbial composition independent of postnatal maternal colonization, resulting in a colitogenic microbiome. This microbial dysbiosis is attributed, at least in part, to methyl donor-derived epigenetic changes in the host that modulate mucosal immune development and function.…”
Section: Maternal Supplementation In Ibdmentioning
confidence: 99%
“…This microbial dysbiosis is attributed, at least in part, to methyl donor-derived epigenetic changes in the host that modulate mucosal immune development and function. 57 While this work has intriguing implications for the developmental origins of nutritional imprinting and IBD risk, further studies are needed to unravel how host genetics, environment and the microbiota interact to shape the mucosal epigenetic landscape over time.…”
Section: Maternal Supplementation In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…173 Thus, prenatal nutritional programming can modulate the mammalian host to harbor a colitogenic microbiome. 174 These studies provide important insights into microbespecific immunity through epigenetic regulation. They highlight the intimate interrelationship between expression of immunerelated genes and immunity pathways in the host with compositional and functional differences of the microbiome.…”
Section: Epigenetic Control and Intestinal Microbiotamentioning
confidence: 99%